2016
DOI: 10.1175/jas-d-15-0203.1
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Droplet Collisions in Turbulent Environment: Collision Statistics and Parameterization

Abstract: The purpose of this paper is to quantify the influence of turbulence in collision statistics by separately studying the impacts of computational domain sizes, eddy dissipation rates (EDRs), and droplet sizes and eventually to develop an accurate parameterization of collision kernels. Direct numerical simulations (DNS) were performed with a relatively wide range of EDRs and Taylor microscale Reynolds numbers R l . EDR measures the turbulence intensity levels. DNS model studies have simulated homogeneous turbule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 51 publications
(81 reference statements)
0
59
0
Order By: Relevance
“…Franklin et al (2005) resolved the droplet collisions using an efficient collision detection technique. Chen et al (2016) made changes to allow simulation in larger domain sizes and introduced a new forcing scheme to achieve a statistically steady turbulent dissipation rate. Chen et al (2018) added the local disturbance flow field induced by droplets to obtain accurate turbulent collision efficiencies and droplet collisional growth affected by both the disturbance flow and the turbulence flow.…”
Section: Model Description and Experimental Setupmentioning
confidence: 99%
“…Franklin et al (2005) resolved the droplet collisions using an efficient collision detection technique. Chen et al (2016) made changes to allow simulation in larger domain sizes and introduced a new forcing scheme to achieve a statistically steady turbulent dissipation rate. Chen et al (2018) added the local disturbance flow field induced by droplets to obtain accurate turbulent collision efficiencies and droplet collisional growth affected by both the disturbance flow and the turbulence flow.…”
Section: Model Description and Experimental Setupmentioning
confidence: 99%
“…7). Many studies have revealed other factors on CDR variation, such as functions of different aerosol components and cloud physical dynamics (Sardina et al, 2015;Chen et al, 2016). Furthermore, the relationship between aerosol and precipitation is complex as well.…”
Section: Cloud Droplet Radius (Cdr)mentioning
confidence: 99%
“…Franklin et al (2005) resolved the droplet collisions using an efficient collision detection technique. Chen et al (2016) made changes to allow simulation in 20 larger domain sizes and introduced a new forcing scheme to achieve a statistically steady turbulent dissipation rate. Chen et al (2018) added the local disturbance flow field induced by droplets to obtain accurate turbulent collision efficiencies and droplet collisional growth affected by both the disturbance flow and the turbulence flow.…”
mentioning
confidence: 99%
“…The domain size of each simulation is about 10 cm in each direction, with grid space ≈ 0.1 cm determined by the dissipation rate as explained in Chen et al (2016). It is recognized that droplet condensation in still-air leads to a narrow DSD and DSD broadening by condensation impacted by small-scale turbulence is insignificant.…”
mentioning
confidence: 99%
See 1 more Smart Citation